2010
DOI: 10.1071/bt09172
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology of the rare desert species Eremosparton songoricum (Fabaceae)

Abstract: The pollination ecology of Eremosparton songoricum (Litv.) Vass., a rare desert species endemic to central Asia, was examined by a series of observational studies and manipulative experiments in two natural populations during [2007][2008]. Results showed that the duration of flowering lasted 21 and 23 days, respectively, in Populations A and B from late May to late June in 2008. Anthesis of a single flower often lasted for 3 days. However, if pollinators were excluded, both the anthesis and stigma receptivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…5 Percentage germination and quiescence of scarified seeds (a) and percentage seedling emergence (b) (mean ± SE) of Eremosparton songoricum at different burial depths. Bars with the same letters are not significantly different at P<0.05 according to the LSD multiple comparison test understand the biological and ecological characteristics of this sand dune species for its conservation (Zhang et al 2008;Shi et al 2010). Our controlled experiments and 5-year field investigations indicated that the low seedling recruitment from sexual reproduction is a limiting factor for the regeneration of this species.…”
Section: Discussionmentioning
confidence: 99%
“…5 Percentage germination and quiescence of scarified seeds (a) and percentage seedling emergence (b) (mean ± SE) of Eremosparton songoricum at different burial depths. Bars with the same letters are not significantly different at P<0.05 according to the LSD multiple comparison test understand the biological and ecological characteristics of this sand dune species for its conservation (Zhang et al 2008;Shi et al 2010). Our controlled experiments and 5-year field investigations indicated that the low seedling recruitment from sexual reproduction is a limiting factor for the regeneration of this species.…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination rate in the wild is <3%, and seedling establishment rate is <0.1% (e.g., Shi et al. ; Zhang et al. , ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored mechanisms of its extirpation and success of its conservation measures (e.g., Shi et al. ; Liu et al. ; Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in very variable pollination environments, such as the Atacama Desert, the mixed mating system keeps the population of A. argyrophylla alive (González & Pérez 2010). Numerous studies demonstrated a mixed mating system in species with reduced habitat which probably helps to explain how the species are able to survive over time in small and isolated populations (Hill et al 2008, Gargano et al 2009, Shi et al 2010, Powell et al 2011. In this context, selfing ability and autogamous capacity provide reproductive assurance, producing enable seed production when pollinators or mates are scarce or unavailable, and outcross pollen is insufficient for full fertilization of ovules.…”
Section: Discussionmentioning
confidence: 99%